Metal-plastic hybrid additive manufacturing to realize small-scale self-propelled catalytic engines - Perera, Adhikarige Taniya Kaushalya (2024)
Microengines driven by catalytic decomposition of a fuel have been an interesting research area recently due to their diverse applications, such as environmental monitoring and drug delivery. Literature reports a number of studies on this topic where researchers have made various attempts to manufacture such microengines. Some such methods are deposition of catalytic metal layers on sacrificial photoresists, electrochemical deposition of metal layers on polymeric structures, or 3D printing of structures followed by multi-step loading of structures with catalysts. These methods, even though proven to be effective, are tedious, time-consuming, and expensive. To address these issues, herein we report a 3D printing technique to realize microengines in a simple, rapid, and inexpensive single-step process. The printing of various shapes of microengines is achieved using digital light processing printing of a catalyst resin, where Pd(II) acts as a catalyst resin. The proposed integrated molding process can achieve cost-effective preparation of high-efficiency microengines. We demonstrate the locomotion of these microengines in 30% (w/w) H2O2 through the decomposition of H2O2 to generate oxygen to facilitate the self-propelled locomotion. The study characterizes the microengine based on several factors, such as the role of H2O2, Pd, shape, and design of the microengine, to get a full picture of the self-locomotion of microengines. The study shows that the developed method is feasible to manufacture microengines in a simple, rapid, and inexpensive manner to be suitable for numerous applications such as environmental monitoring, remediation, drug delivery, diagnosis, etc., through the modification of the catalyst resin and fuel, as desired.